Distribution and diversity of commercial mollusc species at shallow depths in the Saloum delta, Senegal - Tine, Mbaye; Thiaw, Modou; Ngom, Moussa; Faye, Serigne Modou Balla Dior; Sembene, Mbacke (Frontiers in Marine Science, 2025)
Shellfish harvesting in Saloum Islands is crucial for economic and socio-cultural income, particularly for women. However, the industry is facing decline in stocks and harvested individuals, necessitating urgent shellfish assessment and mapping in the Saloum Delta. This study aimed to characterize and assess the distribution, diversity and abundance of mollusc species of commercial interest in the Saloum delta. The species collected were identified using determination keys available in the literature. Their spatial distribution was also studied using principal component analysis (PCA) and their abundance and diversity were assessed using conventional ecological indices. Sampling at 17 stations across five villages (Dionewar, Niodior, Palmarin, Falia, and Sangomar) during both harvesting and biological rest periods in 2019–2020 revealed 21 species from 19 families. Notable findings indicated higher species richness in Niodior and Sangomar than in Falia, Dionewar and Palmarin, based on data from both harvesting and biological rest periods. Diversity metrics, including Hill’s N1 (1.61), Shannon’s H’ (1.77), and Shannon-Weaver (0.47), indicated a high overall diversity with a few dominant species (Simpson’s index: 0.564; equitability index: 0.16), emphasizing the critical role of biological rest in sustaining shellfish populations. Senilia senilis, the most commercialized species, emerged as the dominant species across all localities, followed by the less exploited Diplodonta rotundata. Spatial and temporal variations correlated with environmental factors, including bathymetric distribution and delta hydrology, suggesting the need for effective management strategies alongside existing conservation measures. These results, combined with conservation measures already in place such as biological rest, could lead to better management of shellfish stocks in the Saloum Islands.